1985
DOI: 10.1029/tc004i005p00477
|View full text |Cite
|
Sign up to set email alerts
|

Geological manifestations of ridge collision: Evidence from the Golfo de Penas‐Taitao Basin, southern Chile

Abstract: Recent geological and geophysical studies in the southern Andes adjacent to the intersection of the Chile Rise with the Peru‐Chile Trench (ANT‐NAZ‐SAM triple junction) have revealed a number of features and a Neogene geologic history that are unique along the Pacific margin of South America. This history includes (1) development of a Tertiary‐Quaternary marine basin with up to 3 km of sediment infill (Golfo de Penas‐Taitao basin, GTB), (2) disruption of the region by a series of faults with both normal and str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
124
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(130 citation statements)
references
References 7 publications
4
124
0
1
Order By: Relevance
“…Wang et al (2007) reported the first geodetic evidence on the current dextral shear of the LOFS, finding a trench-parallel slip rate of 6.5 mm yr À1 between 42 and 44 S, which accommodates about 75% of the current margin-parallel component of the Nazca-South America relative plate motion. Lange et al (2008) observed local crustal seismicity along a 130 km long segment of the fault at w42 S. At this latitude, the Chiloé block mentioned above has been decoupled from South America by the action of the LOFS (Forsythe and Nelson, 1985;Wang et al, 2007;Melnick et al, 2009).…”
Section: Location and Geo-tectonic Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al (2007) reported the first geodetic evidence on the current dextral shear of the LOFS, finding a trench-parallel slip rate of 6.5 mm yr À1 between 42 and 44 S, which accommodates about 75% of the current margin-parallel component of the Nazca-South America relative plate motion. Lange et al (2008) observed local crustal seismicity along a 130 km long segment of the fault at w42 S. At this latitude, the Chiloé block mentioned above has been decoupled from South America by the action of the LOFS (Forsythe and Nelson, 1985;Wang et al, 2007;Melnick et al, 2009).…”
Section: Location and Geo-tectonic Settingmentioning
confidence: 99%
“…Several consequences of the Chile Ridge subduction beneath the CTJ have been observed including: tectonic erosion, plutonism near the trench and uplift during the Upper Cretaceous in the Taitao Peninsula (Cande and Leslie, 1986), emplacement of an ophiolitic complex in the Taitao Peninsula (Forsythe et al, 1986) and the displacement of a fore-arc sliver (Forsythe and Nelson, 1985;Wang et al, 2007). Another important consequence is the occurrence of a 350 km long volcanic gap within the arc (Ramos and Kay, 1992), whilst in the back-arc zone widespread basaltic-plateau volcanism takes place (e.g.…”
Section: Location and Geo-tectonic Settingmentioning
confidence: 99%
“…N America, Thorkelson and Taylor, 1989; San Quintin (Baja California), Dickinson and Snyder, 1979;Saunders et al, 1987;S California, Johnson and O'Neil, 1984;British Columbia, Bevier, 1983; S Chile, Forsythe and Nelson, 1985;Antarctic Peninsula, Hole, 1988, 1990Hole and Larter 1993;Hole et al, 1991Hole et al, , 1995. In this paper we will concentrate on one of the simplest tectonic scenarios for slab window formation and related magmatism, that of the Antarctic Peninsula.…”
Section: Slab Window Formation and The Geochemistry Of Alkalie Basaltsmentioning
confidence: 99%
“…3 Ma and 0.3 Ma to Present (Cande and Leslie, 1986). The particular confi guration of the active Chile Ridge system, the alternated migration pattern and the change in convergent directions and velocities are expected to induce contrasting stress conditions in the forearc (e.g., Forsythe and Nelson, 1985;Cembrano, 2000, 2004) and the entire belt (Lagabrielle et al, 2004).…”
Section: Introductionmentioning
confidence: 99%